Analysis of β/α Globin Ratio by Using Relative qRT‐PCR for Diagnosis of Beta‐Thalassemia Carriers. Issue 4 (12th July 2013) - Ranjbaran, Reza; Okhovat, Mohammad Ali; Mobarhanfard, Arash; Aboualizadeh, Farzaneh; Abbasi, Mozhdeh; Moezzi, Leili; Golafshan, Habib Allah; Behzad‐Behbahani, Abbas; Bagheri, Mandana; Sharifzadeh, Sedigheh
<x xml:space="preserve">Abstract</x> Background Current routine tests for premarital screening of β‐thalassemia carriers are not applicable for diagnosis of rare atypical minor β‐thalassemia cases. A more specialized laboratory evaluation for them is the measurement of β/α chain synthesis ratio with the assistance of radioactive amino acids. This method is also no longer routinely accessible. Consequently it is required to establish a rapid, trouble‐free, and reliable method that encompasses all the cases of β‐thalassemia carriers. Therefore we have determined β/α‐globin mRNA ratio by applying relative qRT‐PCR in various β‐thalassemia patients. Methods Reticulocytes RNA extraction and subsequent cDNA synthesis were performed, followed by relative qRT‐PCR for α‐ and β‐globin chain genes and <inline-graphic mimetype="image" xlink:href="ark:/27927/pgg271cshjc" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />β‐actin gene as an endogenous reference. <inline-graphic mimetype="image" xlink:href="ark:/27927/pgg271cshht" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />β/α‐Globin gene ratio was then evaluated with the Pfaffl method. Results The mean of β/α ratio was 0.99, 0.81, 0.69, and 0.69 for normal population, minor, intermediate, and major β‐thalassemia, respectively. Approximately 6% of cases with minor thalassemia RBC index and normal HbA2 and having a decreased β/α ratio were located in the minor β‐thalassemia group. The mean of β/α mRNA ratio in normal individuals and minor β‐thalassemia was significantly different with all other groups (P‐value < 0.05). Nevertheless, there was no such association between β/α mRNA ratio in major and intermediate β‐thalassemia. Conclusion According to the significant differences achieved, no overlapping between minor β‐thalassemia and normal group, capability of diagnosing atypical minor β‐thalassemia, and accessibility of this technique, we can declare that this method could be suggested as a routine premarital screening test for β‐thalassemia carriers.